BRIEF SOLUTIONS OF UNDERGROUND GEOLOGICAL PROBLEMS (American Journal of Pedagogical and Educational Research, 2023)
It's roughly like the difference in longevity between a checkerboard game, a multiplication table, and a chess game on asphalt. In our above example, three advantages of the systematic approach are shown: the introduction of the rules of the game, the alignment of the controlled objects based on knowledge, and the symbolic presentation of the methods of discovery of the intellectual field in the still unexplained system.In today's era, simple (two-link) and multi-link, stable and self-developing, controlled and controlled systems, like a game of intelligence, create incomparable opportunities to study the world around us.